Development of public transport information system in UP Diliman - Lipura, Alyssa M.; Palmiano, Hilario Sean O. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
The main objective of this study is to present a plan for an appropriate and workable public transportation in UP Diliman. It aims to determine the infolation and media preference of public transport users and recommend available tedmologies for the vehicle location system and communication systems. A survey was done on the public transport users using stratified sampling. Available technologies were evaluated using multiple criteria. From the survey, information preference was determined to be information on fares, routes, and stops. Media preference was determined to be information boards. The ground-based radio as the vehicle location system was recommended as a result of the evaluation and integrated communication systems was the suitable communication system to be used. Using the result of the survey and evaluation, a system architecture of the public transport information system was developed. It would then serve as a framework for the implementers of the actual project development.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Information storage and retrieval systems -- Transportation; Transportation -- University of the Philippines